2008
DOI: 10.1007/s10194-008-0048-4
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid neuropathologies in migraine: an update on cerebrovascular and cardiovascular aspects

Abstract: Several conditions are comorbid with migraine; our review is focused on the relation between migraine, and cerebrovascular and cardiovascular diseases. Despite many studies showed an association between migraine and patent foramen ovale, it is still not known whether its presence might be causal for the migraine pathogenesis and currently its closure cannot be recommended for migraine prevention. On the contrary, conflicting epidemiological data link migraine to arterial hypertension and the use of antihyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 120 publications
(112 reference statements)
0
30
0
Order By: Relevance
“…Moreover, in most of the previously published studies, headache patients were identified in the population and investigated for a correlation with the actual levels of BP. The criteria used to diagnose migraine or hypertension were often different from the officially recognized criteria [19,29]. These limitations were avoided in the MIRACLES study which was conducted at general practice level; hypertension and migraine were diagnosed according to international guidelines criteria [7,31,32]; and selection criteria were adopted to limit bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in most of the previously published studies, headache patients were identified in the population and investigated for a correlation with the actual levels of BP. The criteria used to diagnose migraine or hypertension were often different from the officially recognized criteria [19,29]. These limitations were avoided in the MIRACLES study which was conducted at general practice level; hypertension and migraine were diagnosed according to international guidelines criteria [7,31,32]; and selection criteria were adopted to limit bias.…”
Section: Discussionmentioning
confidence: 99%
“…Although both hypertension and migraine have a high prevalence in the population, only few studies have investigated their comorbidity [20][21][22][23][24][25][26][27], sometimes with contradictory results [19,28,29]. The MIRACLES (MIgraine and hypeRtension relAtionship: Comorbidity and risk of cerebrovascuLar EventS) cross-sectional survey was designed to provide further information on three issues related to migraine and hypertension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A right-to-left shunt (RLS) might be implicated in the pathogenesis of this disorder [3]. However, whether patients with atrial septal defect (ASD) have a high prevalence of migraine remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although the evidence supporting an etiologic relationship between migraine and ischemic stroke risk is substantial (Cole & Kittner 2010; Sacco et al 2012; Sacco et al 2008; Sacco et al 2006), the precise mechanism(s) driving this relationship remains uncertain. Stroke, which typically affects older individuals, can be targeted for prevention by optimizing well-established standard vascular risk factors such as hypertension, diabetes, and hypercholesterolemia, among others.…”
Section: Introductionmentioning
confidence: 99%